Statistical Analysis of Magnetic Field Fluctuations in Coronal Mass Ejection-Driven Sheath Regions - Kilpua, E. K. J.; Good, S. W.; Ala-Lahti, M.; Osmane, A.; Fontaine, D.; Hadid, L.; Janvier, M.; Yordanova, E. (Frontiers in Astronomy and Space Sciences, 2021)
We report a statistical analysis of magnetic field fluctuations in 79 coronal mass ejection (CME)-driven sheath regions that were observed in the near-Earth solar wind. Wind high-resolution magnetic field data are used to investigate 2-hour regions adjacent to the shock and ejecta leading edge (Near-Shock and Near-LE regions, respectively) and the results are compared to a 2-hour region upstream of the shock. The inertial range spectral indices in the sheaths are found to be mostly steeper than the Kolmogorov -5/3 index and steeper than in the solar wind ahead. We did not find indications of a f^-1 spectrum, implying that magnetic fluctuation properties in CME sheaths differ significantly from planetary magnetosheaths and that CME-driven shocks do not reset the solar wind turbulence to a similar extent as planetary bow shocks. However, our study suggests that new compressible fluctuations are generated in the sheath for a wide variety of shock/upstream conditions. Fluctuation properties particularly differed between the Near-Shock region and the solar wind ahead. A strong positive correlation was found between the mean magnetic compressibility upstream and downstream regions, but the compressibility values in sheaths were similar to that in the slow solar wind (< 0.2), regardless of the value in the preceding wind. Otherwise, we did not find clear correlations between the inertial range spectral indices in the sheaths and shock/preceding solar wind properties, nor with the mean normalized fluctuation amplitudes. Correlations were also considerably lower in the Near-LE region than in the Near-Shock region. Intermittency was also considerably higher in the sheath than in the upstream wind according to several proxies, particularly so in the Near-Shock region. Fluctuations in the sheath exhibit larger rotation than upstream, implying the presence of strong current sheets in the sheath that can add to intermittency.